2020
DOI: 10.1002/chem.202001722
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of α‐Branched Side Chains on the Structural and Opto‐Electronic Properties of Poly(Diketopyrrolopyrrole‐alt‐Terthiophene)

Abstract: Introducing solubilizing α‐branched alkyl chains on a poly(diketopyrrolopyrrole‐alt‐terthiophene) results in a dramatic change of the structural, optical, and electronic properties compared to the isomeric polymer carrying β‐branched alkyl side chains. When branched at the α‐position the alkyl substituent creates a steric hindrance that reduces the tendency of the polymer to π–π stack and endows the material with a much higher solubility in common organic solvents. The wider π–π stacking and reduced tendency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The vibrational splitting is characteristic for aggregated DPP polymers. 55 Comparison of the temperature-dependent absorption spectra of both polymers (Figure S1, Supporting Information ) in TCE shows that the regioregular polymer retains this higher ratio between the 0–0 and 0–1 vibronic peaks at elevated temperatures. This indicates that the regioregular polymer has a higher degree of aggregation than the regiorandom polymer.…”
Section: Resultsmentioning
confidence: 98%
“…The vibrational splitting is characteristic for aggregated DPP polymers. 55 Comparison of the temperature-dependent absorption spectra of both polymers (Figure S1, Supporting Information ) in TCE shows that the regioregular polymer retains this higher ratio between the 0–0 and 0–1 vibronic peaks at elevated temperatures. This indicates that the regioregular polymer has a higher degree of aggregation than the regiorandom polymer.…”
Section: Resultsmentioning
confidence: 98%
“… 48 The low reaction yield for a is related to the use of a secondary bromoalkane, rather than a primary one and is typical for the synthesis of α-branched DPP molecules. 49 Subsequent bromination to c gave a yield of 86%. The yield of the bromination reaction with NBS is not strongly influenced by the branching of the alkyl side chain.…”
Section: Resultsmentioning
confidence: 99%
“…42 Janssen et al reported α-and β-branched alkyl sidechain-substituted DPP-based polymer donors (1'HD-PDPP3T and 2'HD-PDPP3T) to investigate the effect of sidechains on the structural and optoelectronic properties. 43 backbones. 49 The synthesized region-regular asymmetric polymer (P(TDPPPy-T)-reg) showed a stronger vibronic peak and narrower bandgap (1.49 eV) than those of the random polymer (P(TDPPPy-T)-ran, E g = 1.53 eV).…”
Section: Dpp-based Narrow-bandgap Polymersmentioning
confidence: 99%